2014
DOI: 10.1371/journal.pone.0112699
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Prevents H2O2-Induced HUVEC Senescence by Stimulating Sirtuin-1 Pathway

Abstract: PurposesWe have previously reported that Ginsenoside Rb1 may effectively prevent HUVECs from senescence, however, the detailed mechanism has not demonstrated up to now. Recent studies have shown that sirtuin-1 (Sirt1) plays an important role in the development of endothelial senescence. The purpose of this study was to explore whether Sirt1 is involved in the action of Ginsenoside Rb1 regarding protection against H2O2-induced HUVEC Senescence.Methods and ResultsSenescence induced by hydrogen peroxide (H2O2) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 47 publications
8
45
0
Order By: Relevance
“…effects in diet-induced obese rats (15). Our recent study demonstrated that Rb1 pretreatment prevents human umbilical vein endothelial cell (HUVEC) senescence through modulation of the redox status and protects HUVECs from hydrogen peroxide (H 2 O 2 )-induced senescence through stimulation of the Sirtuin 1 pathway (16). However, limited data have been reported concerning the effect of Rb1 on FFA-induced inflammation in adipocytes.…”
Section: Ginsenoside Rb1 Inhibits Free Fatty Acids-induced Oxidativementioning
confidence: 99%
“…effects in diet-induced obese rats (15). Our recent study demonstrated that Rb1 pretreatment prevents human umbilical vein endothelial cell (HUVEC) senescence through modulation of the redox status and protects HUVECs from hydrogen peroxide (H 2 O 2 )-induced senescence through stimulation of the Sirtuin 1 pathway (16). However, limited data have been reported concerning the effect of Rb1 on FFA-induced inflammation in adipocytes.…”
Section: Ginsenoside Rb1 Inhibits Free Fatty Acids-induced Oxidativementioning
confidence: 99%
“…In vitro experiments have sufficiently proved that oxidative stressors (e.g. H 2 O 2 and ox-LDL) could mimic the oxidative environment and lead to endothelial cells activation and elevation of adhesion molecule and chemokine expression (Song et al, 2014). H 2 O 2 can up-regulate CAMs' expression leading to monocytes adhesion to endothelial cells through the activation of NF-κB and MAPK signaling pathways and ultimately induce endothelial dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that SIRT1 can promote lifespan in higher organisms above yeast and metazoans [32], meanwhile promoting the protection of endothelial cells during oxidant stress exposure [14, 15]. Damaged mitochondria are thought to release more ROS and set in motion a vicious cycle of increasing DNA damage leading to increased ROS production that in turn leads to more DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is an NAD-dependent deacetylase and modulates many biological processes, including oxidative stress, energy metabolism, cell differentiation, and genomic stability [13]. It has been reported that SIRT1 offered significant protection for cell survival in a number of disorders during oxidative stress [14, 15]. …”
Section: Introductionmentioning
confidence: 99%